Inhaler device feature preferences among patients with obstructive lung diseases: A systematic review and meta-analysis. Issue 25 (19th June 2020) - Navaie, Maryam; Dembek, Carole; Cho-Reyes, Soojin; Yeh, Karen; Celli, Bartolome R.
Abstract: Background: Bronchodilators administered through inhalation devices are the mainstay treatment for patients with obstructive lung diseases. Patients do not view devices as interchangeable. This systematic review and meta-analysis examined device feature preferences among patients with obstructive lung diseases treated with handheld inhalers. Study Appraisal and Synthesis Methods: PubMed, EMBASE, PsycINFO, Cochrane, and Google Scholar were searched to identify publications between 2010 and 2019 that met the following criteria: English language; studied adults with chronic obstructive pulmonary disease, bronchitis, or emphysema; and reported patients' device feature preferences specific to metered-dose inhalers, dry powder inhalers, and soft mist inhalers. A manual search extended the study period from 2001 to 2019. Random-effects models were used to generate pooled mean effect sizes and 95% confidence intervals (CIs) for preferred device features. Heterogeneity was measured by the I 2 statistic. Results: Nineteen studies (n = 11, 256) were included in this meta-analysis. Average age ranged from 50.4 to 74.3 years. The majority of patients were male (57%) and had chronic obstructive pulmonary disease (92%). Patients preferred the following device features: small size (71.7%, 95% CI: 46.3, 97.1; n = 604, 3 studies); rapid medication administration (64.9%, 95% CI: 36.5, 93.4; n = 745, 3 studies); durability (62.1%, 95% CI: 39.7, 84.4; n = 4, 500, 4 studies); a dose counter (52.3%, 95% CI: 20.7, 83.9; n = 4, 536, 4 studies); portability (51.8%, 95% CI: 29.1, 74.5; n = 4, 975, 7 studies); perceived ease of use (51.2%, 95% CI: 35.6, 66.7; n = 5, 878, 10 studies); and perceived ease of dose preparation (50.1%, 95% CI: 26.2, 73.9; n = 4, 003, 4 studies). Conclusions and Implications of Key Findings: Adults with obstructive lung diseases preferred small inhaler devices that were portable, durable, perceived as easy to use, and fast in medication administration. Healthcare providers should give due consideration to the patient's device feature preferences when developing a treatment plan that prescribes an inhalation device.